"Analysis of 58 cases of Tinea Capitis in Tehran Razi Hospital " - "Hallaji Z; Sadri MF; Dadvar F " (Acta Medica Iranica, 2001)
Tinea capities is the commonest dermatophytosis in children with diverse clinical presentations. The causative fungi of Tinea capitis vary with geographic area and time.This study was aimed to identify the etiologic agents and determine the related factors of Tinea capitis in Tehran, Iran. From clinically suspected cases of Tinea capitis, microscopy and culture were performed. Of 58patients 96% were children below 12 years of age with the male/ female ratio of 21, the common clinical manifestation was gray patch, followed by kerion, favus (scutula), black dot not seborrehic dermatitis- liker lesion, thrychophyton violaceum was the most common etiologic agent, responsible for 53.4% of infection, followed by T. shoepnleini (24.1%) Microsporum canis (5.5%) , T. mentagrophytes (3.4%) , T. tonsurans (1.7%) and M. gypseum (1.7%). T. violaceum was the predominat pathogen causing Tinea capitis in this region and gave rise to a varied clinical picture